Structural basis for the interaction between the cell polarity proteins Par3 and Par6. - Renschler, F.A.; Bruekner, S.R.; Salomon, P.L.; Mukherjee, A.; Kullmann, L.; Schütz-Stoffregen, M.C.; Henzler, C.; Pawson, T.; Krahn, M.P.; Wiesner, S. (Science signaling, 2018)
Polarity is a fundamental property of most cell types. The Par protein complex is a major driving force in generating asymmetrically localized protein networks and consists of atypical protein kinase C (aPKC), Par3, and Par6. Dysfunction of this complex causes developmental abnormalities and diseases such as cancer. We identified a PDZ domain-binding motif in Par6 that was essential for its interaction with Par3 in vitro and for Par3-mediated membrane localization of Par6 in cultured cells. In fly embryos, we observed that the PDZ domain-binding motif was functionally redundant with the PDZ domain in targeting Par6 to the cortex of epithelial cells. Our structural analyses by x-ray crystallography and NMR spectroscopy showed that both the PDZ1 and PDZ3 domains but not the PDZ2 domain in Par3 engaged in a canonical interaction with the PDZ domain-binding motif in Par6. Par3 thus has the potential to recruit two Par6 proteins simultaneously, which may facilitate the assembly of polarity protein networks through multivalent PDZ domain interactions.